CRITICAL INCIDENTS IN INCLUSIVE EDUCATION: REPRODUCTION SUPPORTED BY THE LAW OF A STATUS QUO (PERcursos Linguísticos, 2024)
ABSTRACT: Considering education as a right for all (Brasil, 1988), we perceive the need to adapt the teaching and learning processes to guarantee their quality and inclusion (Brasil, 2015), contemplating the needs of students who are the target audience of the special education. However, the downward imposition of these demands, without training assistance for the teacher (a subject directly related to law enforcement) and physical and mental infrastructure, implies the occurrence of critical incidents (Seccato, 2020). The present article aims to investigate this dichotomy between theory and practice in inclusive education scenarios, more specifically in foreign languages, triggered by the experience report of four teachers from the basic education. Based on the concept of reproduction (Bordieu; Passeron, 2009) and studies developed by Bezerra (2013) and Fontana (2017), some inconsistencies and inadequate response to the demands presented were found, with the main conditioning factor being the obstacles faced by teachers, originated from for the mistreatment of their jobs (Medrado et al., 2015), especially for the lack of support from macrostructures in initial and continuing education for real inclusion actions culminating in the maintenance of excluding practices, masked by a plastic idea of inclusive education.KEYWORDS: Inclusive education. Foreign languages teaching and learning. Teacher’s education.
Keywords: Inclusive education. Foreign languages teaching and learning. Teacher’s education.